Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fpsyg.2016.00595
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Visual-Auditory Self-Motion Perception during a Simulated Driving Task

Abstract: Recent evidence suggests that visual-auditory cue integration may change as a function of age such that integration is heightened among older adults. Our goal was to determine whether these changes in multisensory integration are also observed in the context of self-motion perception under realistic task constraints. Thus, we developed a simulated driving paradigm in which we provided older and younger adults with visual motion cues (i.e., optic flow) and systematically manipulated the presence or absence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
(81 reference statements)
4
14
0
Order By: Relevance
“…Observing older people as more susceptible to presence-related feelings sparks interest in understanding the relationship between sensitivity to perceive the stimuliwhere older people are frequently demonstrated to be less capable of identifying smells [58], [59] and with increased impairments related to auditory processing [60], [61] -and the impact of these stimuli in the experience -which, according to our results, were revealed to have a greater impact on older people. In fact, these results are consistent with the findings of a recent study that demonstrated multisensory integration as being enhanced in older adults [62].…”
Section: Correlations Discussionsupporting
confidence: 92%
“…Observing older people as more susceptible to presence-related feelings sparks interest in understanding the relationship between sensitivity to perceive the stimuliwhere older people are frequently demonstrated to be less capable of identifying smells [58], [59] and with increased impairments related to auditory processing [60], [61] -and the impact of these stimuli in the experience -which, according to our results, were revealed to have a greater impact on older people. In fact, these results are consistent with the findings of a recent study that demonstrated multisensory integration as being enhanced in older adults [62].…”
Section: Correlations Discussionsupporting
confidence: 92%
“…Recent reviews indicate that aging increases integration across a range of perceptual domains and behaviors ( Freiherr et al, 2013 ; de Dieuleveult et al, 2017 ). An age-related increase in integration of congruent auditory and visual cues may be beneficial, for example improving driving performance ( Ramkhalawansingh et al, 2016 ). Conversely, integration of incongruent cues achieves a coherent percept at the cost of veridical perception and so greater integration could hinder everyday function in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Results in that study showed that the presentation of a brief click sound at the same time as the discs overlapped was less effective at biasing the perception of the discs' motion in older compared to younger participants, suggesting that audiovisual integration in the context of motion may be reduced in older age, at least as assessed by the bounce-stream illusion. In contrast, another study found that the addition of auditory information resulted in a greater benefit for older compared to younger participants in a task where they were required to maintain a constant driving speed in a driving simulator (Ramkhalawansingh et al, 2016). This result suggested aging does not impair the ability to combine auditory and visual information to estimate the speed of self-motion based on optic flow.…”
Section: Introductionmentioning
confidence: 93%